A Personal Social History of a Typology of Intimate Partner Violence. Issue 2 (June 2017) - Johnson, Michael P.
Abstract: This article is a personal social narrative of the development of my control‐based typology of intimate partner violence (IPV). The influence of friends and colleagues in all aspects of this process was so central and so pervasive that it just did not make sense to me to make this a story only about myself. After I tell the social story of the development of the first version and then later versions of my thinking about types of IPV, I leave the personal realm and lay out the implications of the typology for the question of the relationship between gender and intimate partner violence. Finally, I briefly tie the gender question to the general issues of inequality that have driven me throughout my career.